2021
DOI: 10.1155/2021/9987101
|View full text |Cite
|
Sign up to set email alerts
|

How to Use Advanced Fleet Management System to Promote Energy Saving in Transportation: A Survey of Drivers’ Awareness of Fuel-Saving Factors

Abstract: Despite the broad application of advanced fleet management systems (FMSs) in third-party logistics (3PL) companies, there is a marginally limited understanding of how to employ them to enhance transport energy efficiency. In a case study of a Chinese 3PL company, this paper analyzed data obtained from the online FMS to assess drivers’ awareness of fuel-saving factors. A questionnaire was primarily designed to investigate the drivers’ awareness of fuel-saving factors based on the reliability and validity test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Bankruptcy is inevitable if the financial burden and agency costs faced by the business are large enough that the business itself cannot bear it. Therefore, it is concluded that the optimal debt financing structure of an enterprise should be when its debt burden is equal to the marginal cost of agency problems and the marginal benefit brought by its tax savings [6]. Sidloski and Diab considered the contradiction between corporate shareholders and creditors caused by the increase in the proportion of debt financing and also took into account the issue of entrustment and agency within the company; that is, because the principal is the shareholder of the company, the agency cost problem is caused by the unequal information held by the managers of the agency companies and the agency companies [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bankruptcy is inevitable if the financial burden and agency costs faced by the business are large enough that the business itself cannot bear it. Therefore, it is concluded that the optimal debt financing structure of an enterprise should be when its debt burden is equal to the marginal cost of agency problems and the marginal benefit brought by its tax savings [6]. Sidloski and Diab considered the contradiction between corporate shareholders and creditors caused by the increase in the proportion of debt financing and also took into account the issue of entrustment and agency within the company; that is, because the principal is the shareholder of the company, the agency cost problem is caused by the unequal information held by the managers of the agency companies and the agency companies [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang et al obtained the importance of cloud computing for future accounting information construction according to the theoretical research of reality, classified small and medium-sized enterprises by means of qualitative and quantitative cooperation, and then obtained the characteristics of various types of small and medium-sized enterprises. en, according to various characteristics, find out the matching method of cloud computing technology and effective risk management [7]. Lv and Li have developed a cloud computing technology based on the service differential agreement, using the service differential agreement as the basic, according to the feedback questions put forward by users, in order to evaluate different levels of service for cloud computing providers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Particularly, when solving large problems, a major ρ can reduce the impossible amount of pheromone to zero, affecting the global research ability of the algorithm. [25]. A smaller ρ means that the pheromone volatilizes slowly and the residual information dominates the algorithm.…”
Section: Selection Of Volatilization Coefficient ρmentioning
confidence: 99%